THE EFFECT OF CYSTINE AND GLYCOCOLL ON THE OXIDATION OF SODIUM LACTATE BY HYDROGEN PEROXIDE - Ray, George B. (The Rockefeller University Press, 1924)
The rate of production of CO(2) from sodium lactate when treated with H(2)O(2) may be increased by the addition of a compound containing a sulfhydryl group, i.e. cystine. A small part of this increase in rate of CO(2) is due to the action of the amino group as shown by the action of glycocoll. The results tend to show that the mode of action of H(2)O(2) is one of dehydrogenation and that the action of the cystine is comparable to the Atmungskörper of Meyerhof.